Migration and business a survey of Indian communities in the Philippines. - Santarita, Joefe B. (Asian Studies, 2015)
Drawn from archival and library research as well as interviews and focus group discussions, this paper documents the presence of Indian communities in the Philippines. This is contrary to the popular belief that Indians in the country are either Sikhs or Punjabis only. The presence of Indian professionals lately, particularly those who are working in information technology-enabled services sector, as well as students, greatly changes the earlier perception. The existence of these communities further challenges the stereotype that Indians are solely engaged in microfinancing activities. Reality will tell, however, that a good number of Indians are owners of large-scale businesses ranging from textile production to contact centers and pharmaceutical distribution. By and large, these Indian communities and their businesses, dispersed in various provinces, have contributed to the development of Philippine society through job generation, distribution of quality but affordable drugs, and retail and wholesale services among others.